Interface/interphase engineering of polymers for adhesion enhancement: Part II. Theoretical and technological aspects of surface-engineered interphase-interface systems for adhesion enhancement - Gutowski, W.S.; Li, S.; Filippou, C.; Hoobin, P.; Petinakis, S.
Part I of this paper reviewed the theoretical principles of the macromolecular design of polymer interface=interphase systems for obtaining maximum adhesion and fracture performance of adhesively bonded assemblies. In Part II a novel, relatively simple and industry-feasible technology for surface-grafting connector molecules is demonstrated and discussed in detail and supported by a range of experimental examples. It is shown, in agreement with contemporary theory, that the use of chemically attached graft chemicals of controlled spatial geometry and chemical functionality enables a significant increase in the strength and fracture energy of the interphase, to the point of cohesive fracture of the substrate, or that of an adjacent medium such as adhesive, elastomer, or other material. This occurs even after prolonged exposure of investigated systems to adverse environments such as hot water.
Keywords: POLYMERS; SURFACE MODIFICATION; ADHESION; ADHESIVE BONDING; FRACTURE ENERGY; MOLECULAR BRUSHES; ADHESIVES